PENDEKATAN STUDI ISLAM DALAM REHABILITASI PENYALAHGUNA NARKOBA - Amar Ma'ruf (IAIN Purwokerto, 2018)
Abstract: Caring is a form of love and affection from a cultured social human. Narcotics in the view of Islam is an something haram if it is misused. Through caring, prevention of various crimes, juvenile delinquency, security, peace, harmony, will be easily done. With this caring attitude, the motto that,